1995
DOI: 10.1007/bf02228318
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of autogenous and host-derived chemical defenses inOreina leaf beetles (Coleoptera: Chrysomelidae)

Abstract: The pronotal and elytral defensive secretions of 10Oreina species were analyzed. Species feeding on Apiaceae, i.e.,O. frigida andO. viridis, or on Cardueae (Asteraceae), i.e.,O. bidentata, O. coerulea, andO. virgulata, produce species-specific complex mixtures of autogenous cardenolides.O. melanocephala, which feeds onDoronicum clusii (Senecioneae, Asteraceae), devoid of pyrrolizidine alkaloids (PAs) in its leaves, secretes, at best, traces of cardenolides. Sequestration of host-plant PAs was observed in all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 18 publications
0
46
0
1
Order By: Relevance
“…This paper constitutes the first report of the presence of oleanene glycosides in the defensive secretion of a chrysomelid beetle in the genus Leptinotarsa which, until now, was characterized by the production of amino acid derivatives (Pasteels et al 1988(Pasteels et al , 1994Timmermans et al 1992). Preliminary investigation by mass spectrometry of the secretion of yet another Leptinotarsa species, L. calceata, collected on an Asteraceae species near Tatletela (Mexico), demonstrated without ambiguity the presence of still unidentified triterpene glycosides (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper constitutes the first report of the presence of oleanene glycosides in the defensive secretion of a chrysomelid beetle in the genus Leptinotarsa which, until now, was characterized by the production of amino acid derivatives (Pasteels et al 1988(Pasteels et al , 1994Timmermans et al 1992). Preliminary investigation by mass spectrometry of the secretion of yet another Leptinotarsa species, L. calceata, collected on an Asteraceae species near Tatletela (Mexico), demonstrated without ambiguity the presence of still unidentified triterpene glycosides (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In the family Chrysomelidae (leaf beetles), the presence of defensive glands located on the elytra and on the pronotum has been reported for adults of four of the nineteen subfamilies (Pasteels et al 1988(Pasteels et al , 1994. Previous work has shown that adults of the subtribe Chrysomelina (subfamily Chrysomelinae, tribe Chrysomelini) produce isoxazolinone glucosides bearing one or several 3-nitropropanoate moieties (Pasteels et al 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For defense, they secrete secondary metabolites stored in elytral and pronotal exocrine glands (review in Pasteels et al 1988Pasteels et al , 1994. Although some of these compounds are wellknown plant metabolites, they are usually not present in their food plants and are synthesized by the insects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Only few Oreina species, specialized on Senecioneae (Asteraceae) are known to sequester toxic pyrrolizidine alkaloids (PAs) from plants (Hartmann et al 1997;Pasteels et al 1995Pasteels et al , 1996and ref. therein).…”
Section: Introductionmentioning
confidence: 99%